2008
DOI: 10.1080/10623320802092344
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Endothelial Cell Number and Viability Are Reduced by Exposure to High Altitude

Abstract: High altitude and hypoxia are known to induce polycythemia, pulmonary hypertension, and vascular remodeling. The authors investigated a number of blood cell populations in 15 mountain trekkers before and after 12 days spent at >3000 m. Red blood cell and platelet count increased, whereas circulating hematopoietic stem cell (enumerated as CD34bright cells), circulating endothelial cell (CEC) and circulating endothelial progenitor (CEP) count significantly decreased. In particular, the authors observed a decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 26 publications
1
12
1
1
Order By: Relevance
“…To our knowledge, so far few studies have addressed the effects of acute or subacute exposure to hypoxia on EPC homeostasis, yet reporting controversial results. In fact either a reduction (Mancuso et al 2008) or an increase (Theiss et al 2008) in EPCs was found after a 7–12 day sojourn at altitudes ranging from 1700 to 5000 m. By contrast, a 3 h intermittent hypobaric hypoxia exposure equivalent to 5000 m altitude for three consecutive days failed to change EPC concentration in four subjects (Viscor et al 2009), whereas a 1 h bout of normobaric hypoxia equivalent to 4850 m increased EPCs by approximately 70% (Ciulla et al 2007). These conflicting results may depend on a variety of factors, including degree and mode of hypoxia exposure, number and homogeneity of investigated subjects, concomitant physical activity, timing of blood sampling, time‐span before analysis, analytical procedures and inter‐individual variability of the measure.…”
Section: Discussionmentioning
confidence: 97%
“…To our knowledge, so far few studies have addressed the effects of acute or subacute exposure to hypoxia on EPC homeostasis, yet reporting controversial results. In fact either a reduction (Mancuso et al 2008) or an increase (Theiss et al 2008) in EPCs was found after a 7–12 day sojourn at altitudes ranging from 1700 to 5000 m. By contrast, a 3 h intermittent hypobaric hypoxia exposure equivalent to 5000 m altitude for three consecutive days failed to change EPC concentration in four subjects (Viscor et al 2009), whereas a 1 h bout of normobaric hypoxia equivalent to 4850 m increased EPCs by approximately 70% (Ciulla et al 2007). These conflicting results may depend on a variety of factors, including degree and mode of hypoxia exposure, number and homogeneity of investigated subjects, concomitant physical activity, timing of blood sampling, time‐span before analysis, analytical procedures and inter‐individual variability of the measure.…”
Section: Discussionmentioning
confidence: 97%
“…Specifically, hypoxia decreased CPC count in two normobaric hypoxia studies involving a total of 20 subjects [32,33], and also in a hypobaric hypoxia study with 15 mountain trekkers [34]. Different types and intensities of physical exercise have also been shown to be capable of mobilizing CPC.…”
Section: Discussionmentioning
confidence: 99%
“…[7] A study on the effect of exposure to high altitude showed that these endothelial populations were reduced after high altitude exposure for 12 days in 15 mountain trekkers. [8] On the other hand, both CECs and CPCs are reportedly unchanged in obstructive sleep apnea without manifestations of PAH. [9] Furthermore, in the study on EPCs in SSc-PAH, [7] it was suggested that there is an increase in EPCs in the initial stage of PAH, when EPCs contribute to pathologic vascular remodeling.…”
Section: Commentarymentioning
confidence: 98%